Risk Management and Government Internal Control System (SPIP) on Government Financial Performance - Nur Islami, Annisa; Furqan, Andi Chairil; Kamase, Haryono Pasang (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study investigates the influence of risk management and the Government Internal Control System (SPIP) on the financial performance of local governments in Indonesia. The research employs data from provincial, regency, and city governments for the 2021–2022 period, resulting in a final sample of 1,080 observations selected using purposive sampling. Through multiple linear regression analysis, the results reveal that both risk management and SPIP have a significant positive effect on enhancing local government financial performance. These findings highlight the necessity of strengthening risk management and internal control mechanisms to achieve more transparent, accountable, and efficient financial governance across regions, ultimately improving local fiscal outcomes. Future studies are recommended to broaden the scope by including local governments with varying economic and geographic contexts to gain a more comprehensive perspective. Additionally, incorporating external factors such as social conditions, local policies, and adopting qualitative methods like interviews or field observations could provide deeper insights into SPIP and risk management implementation.